2001
DOI: 10.4064/sm146-1-5
|View full text |Cite
|
Sign up to set email alerts
|

A new characterization of Eberlein compacta

Abstract: Abstract. We give a sufficient and necessary condition for a Radon-Nikodým compact space to be Eberlein compact in terms of a separable fibre connecting weak-* and norm approximation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They have become a prominent tool in renorming theory after the seminal paper of Hansell [27], who showed that different kind of networks in Banach spaces are related to fragmentability properties [31]. The linking separability property (LSP, for short), is another tool we have used to connect networks for different metric spaces [32,34,35]. Dow et al [13] have characterized quite recently the LSP in terms of a network condition too.…”
Section: Network For C 1 (X)mentioning
confidence: 99%
See 1 more Smart Citation
“…They have become a prominent tool in renorming theory after the seminal paper of Hansell [27], who showed that different kind of networks in Banach spaces are related to fragmentability properties [31]. The linking separability property (LSP, for short), is another tool we have used to connect networks for different metric spaces [32,34,35]. Dow et al [13] have characterized quite recently the LSP in terms of a network condition too.…”
Section: Network For C 1 (X)mentioning
confidence: 99%
“…Since the seminal paper by Amir and Lindenstrauss [1], where they showed the interplay between topological and geometrical properties of the so-called weakly compactly generated Banach spaces, a lot of research has been done on this class of Banach spaces and their relatives such as weakly K-analytic, weakly countably determined and weakly Lindelöf determined Banach spaces [3,8,16,26,34,35,38,39,42,44,45].…”
Section: Introductionmentioning
confidence: 99%